Significance of Upbringing the Future Teachers, Its Three Factors, Social Importance and Main Root - Ilkhomovna, Zokirova Umida; Abduhakimovna, Sanaqulova Zilola; Norpo'latovna, Soyibnazarova Muqaddas; Ilxomovna, Otaboboyeva Feruza (International Journal of Psychosocial Rehabilitation, 2020)
in this article, the opinions about significance and principles of upbringing future pedagogues in higher educational institutions and also the words of wisdom about self-awareness, told by the ancestors are stated.